Lysine availability in protein-alginate ester gels - Mohamed, Suhaila; Stainsby, George (Elsevier, 1984)
The reduction in available lysine through the interaction of ε-amino groups with propylene glycol alginate to form thermostable gels was investigated using three methods—FDNB, formol titration and dyebinding. Formol titration is preferred for reliability and rapidity. The available lysine content was reduced by at most 18% for disordered proteins (gelatin, caseinate) and from 11 to 18% for structural proteins (whey, soya, egg albumen). The gels are readily attacked by the main digestive proteolytic enzymes, pepsin and trypsin.